Kepemilikan Manajerial dan Kepemilikan Institusional sebagai Determinan Struktur Modal dan Persistensi Laba - Evada Dewata; Yuliana Sari; Eka Jumarni Fithri (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2016)
This study aimed to assess the effect of managerial ownership and institutional ownership of the capital structure and the implications for corporate earnings persistence. The research sample consist of 60 companies during the period 2012 to 2014 based purposive sampling method, then the data was analysed using multiple regression analysis and research panel data by Eviews 9. The results of this study showed that there was a significant negative effect of managerial ownership and institutional ownership partially on capital structure, and simultaneous possession of managerial and institutional ownership has a significant effect on capital structure. Furthermore, there is a significant positive effect of managerial ownership on earnings persistence, there is no significant effect of institutional ownership on earnings persistence, and there is a significant negative effect of earnings persistence on the capital structure. Simultaneously, managerial ownership, institutional ownership and capital structure significantly influence the persistence of earnings.